1977
DOI: 10.1093/ajcn/30.12.1974
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in protein-calorie malnutrition

Abstract: Cytogenetic studies were carried out in five children suffering from moderate to severe protein calorie malnutrition and five healthy controls, using direct preparations of bone marrow using conventional techniques. In the control group there were two abnormalities out of 152 plates analyzed, and in the malnutrition group there were 16 out of 186. This difference is statistically significant, P less than 0.005, implying that chromosomal abnormalities are more frequent in protein calorie malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Likewise, Cervantes-Ríos and coworkers [70] reported the induction of micronuclei in reticulocytes of children with malnutrition and infections but Celik and coworkers [71] did not found DNA damage increase in marasmus cases. In addition, some results were reported in mice or rats fed with low-protein diets who exhibit high rates of chromosomal damage [24,[72][73][74] and citomolecular damage showed by the alkaline single cell electrophoresis assay [75].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Cervantes-Ríos and coworkers [70] reported the induction of micronuclei in reticulocytes of children with malnutrition and infections but Celik and coworkers [71] did not found DNA damage increase in marasmus cases. In addition, some results were reported in mice or rats fed with low-protein diets who exhibit high rates of chromosomal damage [24,[72][73][74] and citomolecular damage showed by the alkaline single cell electrophoresis assay [75].…”
Section: Discussionmentioning
confidence: 99%
“…Interruption of folate/methyl group pathways could plausibly account for both increased risk of OSCM and evidence of DNA and chromosomal damage [22][23][24][25][26] which have been observed in SCM. This preliminary exploration is thus useful as a generator of a specific, testable version of our more general original hypothesis: that is, this study provides estimates which can guide the design and conduct of studies with sufficient power to detect effects of the postulated size.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosome fragments and malsegregated chromosomes are enveloped in their own nuclear membrane forming a small nucleus alongside the larger nucleus within a cell hence the term ‘micronucleus’. In the 1970s, it was also observed that children with protein calorie deficiency have significantly higher chromosome damage than well‐nourished children providing a possible molecular genetic explanation for the developmental defects associated with this macronutrient deficiency condition …”
mentioning
confidence: 99%
“…In the 1970s, it was also observed that children with protein calorie deficiency have significantly higher chromosome damage than well-nourished children providing a possible molecular genetic explanation for the developmental defects associated with this macronutrient deficiency condition. 12 Specific nutrient deficiencies can affect different aspects of DNA metabolism. For example, folate deficiency causes defects in nucleotide synthesis, particularly thymidine synthesis, resulting in the accumulation of its precursor uridine and replacement of thymidine by uracil in DNA, which is highly mutagenic; this effect is further exacerbated by deficiency of vitamin B12 and/or B6, which are required to convert folate to a form necessary for thymidine synthesis 13 Furthermore, minerals such as magnesium and zinc are essential as cofactors for the activity of DNA polymerases involved in DNA replication and repair.…”
mentioning
confidence: 99%